1998
DOI: 10.1039/a707457c
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization of environmental and industrial particulate samples†

Abstract: The characterization of particles, especially aerosol particles, is of great importance to many scientific fields. A relevant brief overview is given. A rigorous scheme of sampling and in-depth characterization of particulate samples has been developed in the authors' laboratories and by collaborative groups, including investigations by the following techniques: total reflection X-ray fluorescence spectrometry for quantitative bulk characterization; solid-state speciation by valence band X-ray spectrometry usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 44 publications
(62 reference statements)
0
20
0
Order By: Relevance
“…Emission factors for CNT/FULs from common combustion sources have not been published to our knowledge, though these morphologies have been identified in exhaust from natural gas (NG) stoves (Murr et al 2004) and tentatively from a 157 diesel engine (Evelyn et al 2003) and gasoline engines (Ortner et al 1998). Blom et al (2000) found structures that might have been FULs but were not identified as such by those authors.…”
Section: Introductionmentioning
confidence: 97%
“…Emission factors for CNT/FULs from common combustion sources have not been published to our knowledge, though these morphologies have been identified in exhaust from natural gas (NG) stoves (Murr et al 2004) and tentatively from a 157 diesel engine (Evelyn et al 2003) and gasoline engines (Ortner et al 1998). Blom et al (2000) found structures that might have been FULs but were not identified as such by those authors.…”
Section: Introductionmentioning
confidence: 97%
“…There are several methods and instruments for studying different properties of the surface of airborne particulate matter (PM), ranging from morphology to elemental composition (Braun et al, 2007;Coury and Dillner, 2008;Faude and Goschnick, 1997;Kirchner et al, 2003;Ortner et al, 1998;Osan et al, 2006;Zelenay et al, 2011;Zhu et al, 2001). The use of X-ray Photoelectron Spectroscopy (XPS) for chemical surface analysis of airborne particles is not a routine method in environmental applications.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous methods have been applied to the analysis of single aerosol particles and have been well documented in a number of sources (Grasserbauer 1983;Fletcher & Small 1993;Ortner et al 1998;De Bock & Van Grieken 1999). The vast majority of available methods are limited by spatial resolution and/or detection limits, and tend to be more applicable to the analysis of particles 0.5 m m to 1 m m in diameter and above.…”
Section: Single Ultra¯ne Particle Analysis Methodsmentioning
confidence: 99%